Structure and Function of Platelet Glycocalicin - Jamieson, G A; Okumura, T; Hasitz, M (Thrombosis and Haemostasis, 1979)
Present knowledge of the structure and function of platelet glycocalicin is reviewed. Glycocalicin (M,. 150,000) is a glycoprotein component of the outer surface of intact platelets which is released in soluble form following platelet homogenization. Glycocalicin has been purified and shown to inhibit platelet aggregation induced by thrombin or by ristocetin. Thrombin binding activity is associated with the peptide “tail” of the molecule (Mr 45,000), the macroglycopeptide portion (Mr 120,000) being without effect. Glycocalicin and membrane-bound glycoprotein I have been shown to be functionally and immunologically identical. Studies with platelets modified by chymotrypsin, and with platelets from patients with Bemard-Soulier disease and an ill-defined bleeding abnormality show that the amount of thrombin bound is proportional to the total amount of glycocalicin and glycoprotein I present. These results support the concept of a single class of binding site for thrombin in platelets.